(untitled) (REMUNOM, 2024)
The objective of the Brazilian penal execution system is to promote the social integration of convicts and internees. Therefore, in addition to the punitive aspect, the legal system recognizes the concern to integrate the convict back into society, using re-socializing measures that lead to the achievement of non-recidivism. To this end, this article discusses the significant contribution made by the use of legal psychology in the process of social reintegration, and also in the development of prisoners through psychological assessment practices, taking into account the individuality of each prisoner and their potential. The approach and study of this research was carried out through bibliographical research in doctrines, legal literature, articles, jurisprudential analysis and legal cases of repercussion in the higher courts.